1986
DOI: 10.1111/j.1439-0450.1986.tb00037.x
|View full text |Cite
|
Sign up to set email alerts
|

A Sero‐Epidemiological Survey of Infections with the Bovine Respiratory Syncytial Virus in First‐Season Grazing Calves

Abstract: Summary A sero‐epidemiological survey of Bovine Respiratory Syncytial Virus infections in calves was carried out on 123 dairy farms in the Netherlands. During the last weeks of November 1983 5 first season grazing calves per farm were blood sampled. The presence of antibodies against the Bovine Respiratory Syncytial Virus (BRSV) was determined by the Enzyme Linked Immuno Sorbent Assay. The mean extinction values per farm were related to farm‐herd‐ and management characteristics. It was found that 1) On 95% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Housing young heifers in the same building with older ones (Kimman et al, 1988) or with adult cattle (Virtala et al, 1999) has been reported to increase the risk of BRD. Accordingly, Ploeger et al (1986) reported a negative relationship between the onset of a clinical BRSV infection and contact of young heifers with older cattle at pasture or after stabling. Contrary to what is often assumed, several others found no association between housing and BRD (Perez et al, 1990;Curtis et al, 1993;Van Donkersgoed et al, 1993).…”
Section: Housingmentioning
confidence: 99%
“…Housing young heifers in the same building with older ones (Kimman et al, 1988) or with adult cattle (Virtala et al, 1999) has been reported to increase the risk of BRD. Accordingly, Ploeger et al (1986) reported a negative relationship between the onset of a clinical BRSV infection and contact of young heifers with older cattle at pasture or after stabling. Contrary to what is often assumed, several others found no association between housing and BRD (Perez et al, 1990;Curtis et al, 1993;Van Donkersgoed et al, 1993).…”
Section: Housingmentioning
confidence: 99%
“…6 For HRSV, vaccine development began more than 3 decades ago, but this goal still remains to be achieved. 7,8 For BRSV, attenuated-live and inactivated (killed) vaccines are marketed and have had conflicting reports 3,[9][10][11] of efficacy. Also, for most licensed BRSV vaccines, there are no published data that indicate efficacy in calves with maternal antibodies.…”
mentioning
confidence: 99%
“…There are conflicting reports on the possible effects of live and inactivated vaccination on the prevalence of BRSV infections. Several workers have reported that vaccinations reduced the prevalence and severity of the disease (Kubota et al, 1992(Kubota et al, , 1990Howard et al, 1987;Stott et al, 1987Stott et al, , 1984Morter and Amstutz, 1986;Thomas et al, 1986;Frennet et al, 1984) while others found no significant effect (Morisse et al, 1990;Ploeger et al, 1986;Holzhauer and Wertenbroek, 1979). A major limitation of these vaccines is that maternally-derived antibody to BRSV suppresses an active immune response in calves Westenbrink et al, 1989).…”
Section: Limnunity and Immunizationmentioning
confidence: 99%